Knovel polymer matrix composites database.
The purpose of this database is to satisfy the needs of engineers for comprehensive data for polymer-matrix composites. The unique compilation of high-quality typical and design data for prepregs, matrix resins and fiber reinforcement enables insightful decision making for engineers involved in material selection and performance modeling. To support those tasks, the emphasis is on providing tensile, shear, flexural, compressive and fatigue properties of composites, cured under different conditions and tested in a wide range of temperature and stress conditions.